Galactia glaucescens KUNTH – FABACEAE (Leguminosae): STATE-OF-THE-ART - Florenziano, Rosimere Farias de Mendonça; dos Santos, Marcio Galdino; Gonçalves, Letícia Cristina; Oshima-Franco, Yoko (Seven Editora, 2026)
Galactia glaucescens Kunth is a native species from South America whose traditional use is mainly associated with antivenom properties. Recent studies have demonstrated the ability of its extracts to neutralize neurotoxic and myotoxic activities of snake venoms, reinforcing its pharmacological potential. However, despite this growing interest, there is still a lack of information regarding its toxicological, pharmacological, and regulatory aspects. Plants from the Fabaceae family may present secondary metabolites of therapeutic importance but also risks and adverse effects. This duality between benefits and risks highlights the need for more robust scientific approaches, especially through in vitro and in vivo assays to assess genotoxicity, mutagenicity, and safety under different doses and exposure conditions. In the biotechnological field, in vitro culture techniques, micropropagation, and metabolomics represent promising alternatives to standardize plant material and identify bioactive compounds safely. Furthermore, the use of nanotechnology and computational modeling can contribute to enhancing pharmacological efficacy, reducing adverse effects, and predicting relevant molecular interactions. Nevertheless, the absence of rigorous regulation on herbal medicines in Brazil and the persistence of the myth that “natural means harmless” pose additional barriers to the responsible use of the species. It is concluded that G. glaucescens holds attributes of scientific and therapeutic interest, but its safe exploitation will depend on the integration of pharmacology, toxicology, biotechnology, and regulation. Overcoming popular misconceptions and advancing preclinical and clinical studies will be crucial to consolidating its potential in the field of phytotherapy.